How effective are hiring subsidies in reducing long-term unemployment among prime-aged jobseekers? Evidence from Belgium - Sam Desiere; Bart Cockx (IZA Journal of Labor Policy, 2022)
Hiring subsidies are widely used to create (stable) employment for the long-term unemployed. This paper exploits the abolition of a hiring subsidy targeted at long-term unemployed jobseekers older than 45 years of age in Belgium to evaluate its effectiveness in the short and medium run. Based on a triple-difference methodology, the hiring subsidy is shown to increase the job-finding rate by 13% without any evidence of spillover effects. This effect is driven by a positive effect on individuals with at least a bachelor's degree. However, the hiring subsidy mainly creates temporary short-lived employment: eligible jobseekers are not more likely to find employment that lasts at least 12 consecutive months compared with ineligible jobseekers.
Keywords: H22; J08; J18; J23; J38; J64; J65; J68; 330; hiring subsidies; long-term unemployment; prime-aged jobseekers; triple difference; temporary help agencies